Characteristics of Chinatown-Indies Architecture in Semarang Petudungan Street Row House - Indarti, Fitri Dwi; Syah, Mellisa Putri; Pratiwi, Isna (Architecture Study Program, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2024)
Semarang Chinatown is one of the villages with unique characteristics in Semarang City. Until now, Chinatown still exists, is inhabited, and is active as an economic center. Chinatown continues growing to become one of the most important residential and trading centers in Semarang's crowded and busy city. Chinatown is synonymous with trade because most of the people run trading businesses. Chinatown is one of the settlements famous for its unique typology. Petudungan Street is one of the roads in Semarang Chinatown that connects the main road of Mataram with Semarang Chinatown. This road is located directly adjacent to the Semarang River. House buildings in this area are one of the main factors in the formation of the environment both on a macro and micro scale. The row house buildings in this area have a Chinatown-Indies style because these residential buildings found many things that reflect the creativity of acculturation of Chinese and local cultures. Like having a roof supported by a wall on the edge with openings on the roof. But the façade has a local influence that manifests itself in the panel openings in the form of panel doors.